Charophyte species and communities of different types of water ecosystems of the Ziemia Lubuska region (Western Poland) - Pełechaty, Mariusz; Pukacz, Andrzej (Biodiversity: Research and Conservation, 2006)
The aim of the paper was to present the floristic and phytocoenotic diversity of charophytes (Characeae family) in the aquatic ecosystems of the Ziemia Lubuska region in Poland. Data set was collected during the study of rush and aquatic vegetation carried out between the years 2000 and 2005. From amongst 34 species of the Characeae family expected in Polish waters 21 were found in different aquatic ecosystems of the region of Ziemia Lubuska, representing all 5 genera known from Poland. Considering charophyte vegetation, out of 30 associations 15 were found in the region: 14 in lakes and one in old riverbeds and ponds. Among these associations Charetum hispidae, Charetum intermediae, Lychnothamnetum barbati and Nitelletum opacae were observed sporadically. Considering 50 lakes surveyed, phytocoenoses of charophyte associations were found in 25 of them. In further 13 lakes single specimens, clusters or small patches of charophytes occurred. The highest number of species per lake was 7; it was also the highest number of charophyte communities. The analysis of habitat conditions in lakes revealed that such important parameter as phosphorus content was not involved in the habitat differentiation of lakes with the varied development of charophyte vegetation.